Biologikatherapie nach COVID-19-Infektion: Keine Reaktivierung einer COVID-19-Infektion bei positivem Antikörperstatus SARS-CoV-2 unter Biologikatherapie - Steinchen, N. (Z Rheumatol, 2020)
A case with rheumatoid arthritis and insufficient compensation under disease-modifying combined long-term therapy with methotrexate and leflunomide is reported. After recovery from a COVID-19 infection, a tumor necrosis factor (TNF) inhibitor therapy was initiated. Until now no reactivation of the COVID-19 infection with positive SARS-CoV‑2 antibody status has occurred.